225Actinium-armed antibody targeting CCR8+ regulatory T cells synergizes with immunotherapy to promote tumor rejection in syngeneic colorectal cancer models - Frank, Connor; Xiao, Zhiwen; Allen, Kevin J. H.; Jiao, Rubin; Malo, Mackenzie E.; Dadachova, Ekaterina (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) remains a formidable threat to health worldwide. Immunotherapy with immune checkpoint inhibitors results in only a minority of CRC patients experiencing long-term progression-free survival, at the expense of significant autoimmune toxicity. Development of new therapeutics to “wake up” the immune system to fight CRC is necessary. Here we investigated for the first time radioimmunotherapy (RIT) directed towards CCR8, a marker of tumor-infiltrating immunosuppressive T-regulatory cells (ti-Tregs) as a method to recover anti-tumor immunity followed by immunotherapy in CRC models.Methods225Actinium (225Ac)-labeled anti-CCR8 antibody and anti-CTLA-4 immunotherapy were used to assess their potential synergistic effects in syngeneic murine CRC models CT26 and MC38. The safety of all treatments was assessed through complete blood counts and blood chemistry. 225Ac-anti-CCR8 RIT-treated tumors were analyzed immunohistochemically for FoxP3 and CCR8 expression while mechanistic studies of tumor-infiltrating lymphocytes were done by flow cytometry.Results225Ac-anti-CCR8 RIT alone demonstrated effectiveness in CRC models but dramatic anti-tumor response was observed when it was combined with anti-CTLA-4 immunotherapy. Immunotherapy alone failed to control tumor growth. Tumor immunohistochemistry post 225Ac-anti-CCR8 RIT showed ablation of CCR8+ ti-Tregs while flow cytometry analysis revealed CCR8-specific increased influx of effector CD8+ T cells, M1 macrophages and NK cells in comparison with 225Ac-control antibody.ConclusionsThese data demonstrate a synergistic effect of anti-aCCR8 RIT with immunotherapy through enhancement of adaptive and innate anti-tumor responses. Further investigation of anti-CCR8 RIT as a potential cancer-agnostic agent and its combinations with other immunotherapy agents such as anti-PD-1, LAG3 or TIGIT is warranted.